DIALEKTIKA INTEGRASI ANTARA PSIKOLOGI DAN ISLAM DI INDONESIA: PELUANG BAGI METODE EKSPERIENSIAL - Subhani Kusuma Dewi (UIN Sunan Kalijaga, 2013)
The idea of integration between psychology and Islam in Indonesia has been set up almost two decades. This scientifc discourse philosophically and methodologically illustrates Indonesian Muslim scientists vary in seeing Islam as a paradigm. Analyst identifes the integration can be classifed into two terms, either Islamic psychology (IP) or psychology of Islam (PoI) unfortunately both represent respectively a monodiscipline. If it is so, the integration is likely to reach its failure, since both of the terms entails a new dichotomy instead of an interdisciplinary study. By studying Islamic philosophy of science this paper –on one side- works to highlight a new synthesis within the dynamic of integration process, namely ftrah psychology (Psikologi Fitrah), yet criticize its methodological problem. On the other side, it focuses on the possibility of Islamic studies (Dirasat Islamiyya) in order to offer an adequate method for Muslim spiritual experiences. To that end, this paper proposes two major steps in fnding the method, namely by: 1) proposing falsifable project for two previous generations (IP and PoI); 2) re-examining a ‘self-consciousness’ method through essensial-authentic experience (irfānī) that has been handed down by the classical Islamic thinkers and scientists in Islam.